Respuesta :

Answer:

1: 1/2 or 1 divided by 2

2:

3:

4:

Step-by-step explanation:

\- x + s q r t 1 − x 2 \- = s q r t 2 ( 2 x 2 − 1 ) \- x + s q r t 1 − x 2 \- = s q r t 2 ( 2 x 2 − 1 ) \- x + s q r t 1 − x 2 \- = s q r t 2 ( 2 x 2 − 1 ) \- x + s q r t 1 − x 2 \- = s q r t 2 ( 2 x 2 − 1 ) \- x + s q r t 1 − x 2 \- = s q r t 2 ( 2 x 2 − 1 ) \- x + s q r t 1 − x 2 \- = s q r t 2 ( 2 x 2 − 1 ) \- x + s q r t 1 − x 2 \- = s q r t 2 ( 2 x 2 − 1 ) \- x + s q r t 1 − x 2 \- = s q r t 2 ( 2 x 2 − 1 ) \- x + s q r t 1 − x 2 \- = s q r t 2 ( 2 x 2 − 1 ) \- x + s q r t 1 − x 2 \- = s q r t 2 ( 2 x 2 − 1 ) \- x + s q r t 1 − x 2 \- = s q r t 2 ( 2 x 2 − 1 ) \- x + s q r t

ACCESS MORE